Lasers in the conservation of artworks : proceedings of the International Conference LACONA VII, Madrid, Spain, 17-21 September 2007 /: proceedings of the International Conference LACONA VII, Madrid, Spain, 17-21 September 2007. (©2008) - Unknown
No abstract available